(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
This study aims to understand the role of costumes in the holographic/avatar representation of ABBA members in the “ABBA Voyage” show (2022). Designed by B. Åkerlund, in collaboration with brands such as Dolce & Gabbana, the costumes were approved by the band for subsequent digitalization. The study analyzes the costumes used in the “Abba Voyage” show, through posts on the official Instagram profile (@abbavoyage), between August 2021 and October 2022, official records, and specialized press in order to list the main highlights used to enhance the visual representation of the artists. It is inferred that costumes are fundamental to ABBA’s visual language, and the use of emerging technologies continues to maintain the group’s pop image, providing a reference point for recognizing the artists.